On the specificity of the radical right in Latin America. From Hitler and Mussolini to Rafael Lopez Aliaga - Ubilluz Raygada, Juan Carlos (2021)
This article discusses the presumed connection between the radical right, in Peru and Latin America, and classical fascism, as well as trying to grasp its specificity. As a result of a political, historical and psychoanalytical analysis the author outlines the (dis)continuity between fascism, the radical right in Europe and USA, and the radical right in Peru and Latin America. Whereas the former might be connected to Hitler and Mussolini, the latter is rooted in the colonial tradition and the introduction of neoliberalism through Augusto Pinochet’s coup. However, it’s the common paranoid delusion in which the national community must be saved from an evil enemy that reveals the connection between both radical rights, and allow us to identify them as the same phenomenon (with distinctive features). Indeed, this delusion is described by the author as fundamental in the Peruvian presidential campaign of Rafael Lopez Aliaga, who speared an alliance of neoliberals and evangelicals to oppose a communist conspiracy that sought to destroy a capitalist and conservative country through its “anti-business” and “gender ideology” schemes.